Los procesos de justicia transicional, justicia, verdad y reconciliación en el espacio Francófono y en América Latina (2016)
This article presents a summary of the practical guide published by the “InternationalOrganisation Francophonie, that contains experiences in francophone countries for transitional justice processes, justice, truth and reconciliation; It also explains themain features of the processes carried out in South Africa, Sierra Leone, Argentina,Chile and El Salvador, in order to contribute to the process that takes place inColombia, with a view to consolidating a lasting peace.